Pengaruh Media Sosial terhadap Pembentukan Citra Koprasi Modern di Kalangan Generasi Muda - Dwi Aprilia; Dini Selasi (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2026)
The rapid advancement of information and communication technology has made social media one of the most widely used platforms among young people for accessing information and interacting with others. This phenomenon provides an opportunity for cooperatives to utilize social media as a tool for building a more modern image that aligns with the needs of society in the digital era. This study aims to examine the influence of social media on the formation of a modern cooperative image among the younger generation and to identify its role as a medium for promotion, information dissemination, education, and communication. The study employs a qualitative approach using a library research method. Data were collected from various literature sources, including scientific journals, books, articles, and previous studies related to the research topic. The findings reveal that social media contributes to improving young people's knowledge, interest, and positive perceptions of cooperatives. The delivery of information through engaging and interactive content helps expand outreach and strengthen the image of cooperatives as innovative, professional, and technology-oriented institutions. Therefore, optimizing the use of social media can serve as an important strategy to enhance the attractiveness of cooperatives and encourage greater youth involvement in cooperative development in the future.